Assessment of Ail Gene Marker Amplicon for Molecular Characterization of Pathogenic Yersinia enterocolitica in Food Samples Collected in Iran - MR Khorramizadeh; MM Soltan-Dallal; F Safavifar; F Saadat; S Rezaie; S Hashemi; M Taremi; S Ardalan; MR Zali (Tehran University of Medical Sciences, 2007)
Background: To assess the utility of the chromosomal ail virulence gene sequence for detection of pathogenic Yersinia enterocolitica in raw meet food products (beef, lamb, and chicken). Methods: This study included 39 Yersinia enterocolitica positive cultures from suspicious food samples, in a working period of six months. These samples were referred to the "Food-Borne Diseases and Chronic Diarrhea Lab at Research Centre for Gastric and Liver Diseases" of the Taleghani Hospital at Shahid Beheshti University of Medical Sciences, Tehran, Iran. Isolates from 8 cultured Y. intermedia, Y. aldovi, Y. intermedia type O:45, Y. kristensenii, Y. enterocolitica type O:12/26, Y. enterocolitica type1/7/8, Y. frederiksenii type O:39, and Y. enterocolitica type O:8 samples were included in the study. Four non-Yersinia species Salmonella typhi, Shigella dysenteriae, Shigella flexeneri, and Proteus mirabilis were used for specificity testing. An established Yersinia type O:9 was used as positive control and for sensitivity testing. An in-house real-time PCR assay was designed in order to rapidly and specifically identifies the presence of specific Yersinia species. Results: Out of 39 tested Y. enterocolitica samples, 6(2.3%) showed positive results for the ail gene PCR product, typed as O:8, and O:9, respectively. PCR products were sent for sequencing. Two sequences were registered with the National Center for Biotechnology Information (NCBI Genbank) as polymorphic ail gene sequences under the accession numbers of DQ157767 and DQ003329. Conclusions: Collectively, this test is well adapted for definite confirmation of pathogenic Y. enterocolitica in food samples.